Is the collective listener a passive recipient or a creator of ideas? (about the intentional dimension of music performance - Katrych, Olha (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. The proposed research is determined by the realities of the musical society, they are characterized by the active inclusion of collective listening acceptance in the creation of modern musical projects. The lack of a musicological base determined the strategy of understanding the process of communication in music in the perspective of the achievements in the current communication theory. The ideas of the theory of communication developed by American and Canadian scientists Marshall McLuhan, Harold Innis, and John Durham Peters became the theoretical support of the presented considerations. Communicative strategies of the Socratic-dialogic and evangelical-dispersive type receive scientific approval in the research in the musical and communicative sphere. Main objective of the study is to substantiate of the hypothesis about the nature of musical communication as an act of collective (composer, performer, listener) sound-intonation intentionality, where the creativity or passivity of the reaction of the collective listener directly depends on the performance creativity. The discursive understanding of the role of the collective listener in music is carried out using the complex methodology of scientific knowledge, which combines the methods of theoretical generalization, discourse analysis, comparative studies and empirical observations. Results. For the first time, the definition of musical communication is formulated as a process that unites its participants with the desire (conscious or not) of spiritual development by immersion in acts of musical and intonation creation. Emphasis is placed on the function of individual intentionality of the musical and performing component in communicative processes. The author’s definition of an individual musical and performance style as a system of expressive means corresponding to the specificity of the performer’s musical worldview has been spread. This system, while maintaining its integrity, functions as a supporting factor for the re-intonation of various compositional styles and a guarantor of auditory co-intonation in musical communication processes. Empirical testing of the theoretical generalizations presented in the proposed research is based on the personal professional experience of the author.